Case Report: Genomic Characteristics of the First Known Case of SARS-CoV-2 Imported From Spain to Sichuan, China - Chao Liu (Frontiers Media S.A., 2021)
The pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been basically under control in China since March 2020, but the import of domestic SARS-CoV-2 has begun to increase. This study reported the first case of asymptomatic SARS-CoV-2 infection imported from Spain into Sichuan Province, China, on March 11, 2020. The infected male had a body temperature of 37.5°C, normal blood oxygen saturation levels, and a computed tomography (CT) examination showed that his lungs had no shadows. However, a throat swab from the subject tested positive for SARS-CoV-2 using qPCR assay. In this study, we conducted transcriptome sequencing on respiratory throat swabs from the subject and found that the dominant SARS-CoV-2 sequence (Gene Bank ID: MW301121) was a spike protein D614G mutant strain, which is currently popular throughout world. We downloaded and analyzed SARS-CoV-2 sequences collected from cases in China and Spain for comparison and tracing purposes. After March 11, 2020, the Chinese domestic clade was naturally divided into the imported SARS-CoV-2 D614G mutant strain and evolutionarily-related similar sequences and that of sequences collected in the original Wuhan area. The sequence reported in this study was located on a small branch, far from the evolution of Wuhan sequences. As expected, the identified sequence was closely related to the evolution of the SARS-CoV-2 D614G mutant strain circulating in Spain.